Projecting a nation : Chinese national cinema before 1949 - Hu, Jubin (Hong Kong University Press ; Eurospan, 2003)
The book analyses the wide variety of conceptions of ""Chinese national cinema"" between the early years of the 20th century and 1949, and contrasts these to conceptions of national cinema in Europe and China.